Modernleşme Sürecinde Mısır'da Karma Mahkemeler Kurulması Meselesi - ÖZKAYA, Sevda (International Balkan University, 2014)
In order to have an accurate evaluation of the history of Islamic societies, it is necessary to have a clear idea of what their concept of law is. The concept of law which regulates the social life in many ways has developed differently in the Islamic civilization from that in the Christian Europe. The Europeanization Movement of the 19th century which established itself in administrative, political and social fields also came into prominence in the field of law; and the system law which was regarded as an obstacle to the modernization of the Islamic society was sought to be transformed, thus making a significant stride for the Islamic society toward interacting with the dynamic European society. In the 19th century, that is, a period of modernization for the Islamic society, several economic and politico-social reasons necessitated the aforementioned interaction. The increase in the trade between Ottoman Empire and the Europe gave rise to the intercultural relations. Therefore, within a short period of time, non-Muslims began to settle in the Muslim coastal towns. These non-Muslim settlers, despite being subject to their own laws as a privilege, had also many rights in many fields through capitulations and sometimes exploited them. In consequence of the sharp increase in the trade relations between Egyptian society and the European society from 1841 onwards, readjustments in the Egyptian judiciary became obligatory primarily for settling the commercial-economic issues. One of the significant moves of modernization efforts in Egypt under Ottoman rule was the one in the field of law, and within this context, the question of mixed-tribunals must be examined with a critical point of view.
Keywords: 16. Peace & justice